Informed intermediaries - Paula Onuchic (Theoretical Economics, 2022)
I develop a theory of intermediation in a market where agents meet bilaterally to trade and buyers cannot commit to payments. Some agents observe the past trading history of traders in the market. These informed agents can secure trades by punishing traders who previously defaulted. The punishing strategy affects equilibrium prices and determines which trades are hindered by the risk of default. Intermediation is a robust equilibrium feature, generated by asymmetric punishing strategies that yield informed agents either more effective opportunities to trade or the ability to extract more surplus in trades.
Keywords: D83; D85; 330; Intermediation; limited commitment; bilateral trade; trade network